Protonectin (1-6): A novel chemotactic peptide from the venom of the social wasp Agelaia pallipes pallipes - Baptista-Saidemberg, Nicoli B. [UNESP]; Saidemberg, Daniel M. [UNESP]; de Souza, Bibiana M. [UNESP]; Cesar-Tognoli, Lilian M. M. [UNESP]; Ferreira, Virginia M. R.; Mendes, Maria Anita; dos Santos Cabrera, Marcia P. [UNESP]; Ruggiero Neto, Joao [UNESP]; Palma, Mario Sergio [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Peptides constitute the largest group of Hymenoptera venom toxins; some of them interact with GPCR, being involved with the activation of different types of leukocytes, smooth muscle contraction and neurotoxicity. Most of these toxins vary from dodecapeptides to tetradecapeptides, amidated at their C-teminal amino acid residue. The venoms of social wasps can also contains some tetra-, penta-, hexa- and hepta-peptides, but just a few of them have been structurally and functionally characterized up to now. Protonectin (ILG-TILGLLKGL-NH(2)) is a polyfunctional peptide, presenting mast cell degranulation, release of lactate dehydrogenase (LDH) from mast cells, antibiosis against Gram-positive and Gram-negative bacteria and chemotaxis for polymorphonucleated leukocytes (PMNL), while Protonectin (1-6) (ILGTIL-NH(2)) only presents chemotaxis for PMNL However, the mixture of Protonectin (1-6) with Protonectin in the molar ratio of 1:1 seems to potentiate the biological activities dependent of the membrane perturbation caused by Protonectin, as observed in the increasing of the activities of mast cell degranulation, LDH releasing from mast cells, and antibiosis. Despite both peptides are able to induce PMNL chemotaxis, the mixture of them presents a reduced activity in comparison to the individual peptides. Apparently, when mixed both peptides seems to form a supra-molecular structure, which interact with the receptors responsible for PMNL chemotaxis, disturbing their individual docking with these receptors. In addition to this, a comparison of the sequences of both peptides suggests that the sequence ILGTIL is conserved, suggesting that it must constitute a linear motif for the structural recognition by the specific receptor which induces leukocytes migration. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Wasp venom; Toxin; Chemotaxis; Heterodimer; Peptide-membrane interaction; Mast cell degranulation; Antibiosis